Populism in Africa - Resnick, Danielle (Oxford University Press, 2017)
The populist modifier has been applied frequently in Africa to refer to very distinct phenomena. At the same time, Africa represents an especially challenging case for delineating populism due to the predominance of personalistic leaders and the lack of policy ideology underlying many political parties. Therefore, this chapter argues that a cumulative conceptual approach provides the most analytical leverage in discerning African cases of populism. A cumulative approach aggregates attributes commonly associated with a concept, and the more attributes that exist, the closer an example fits the conceptual ideal. Consequently, the chapter suggests that populism is present only when it manifests as a political strategy bolstered by ideological discourse and socio-cultural performances. The chapter then reviews the utility of this cumulative conceptualism by comparing episodes of populism in Africa over time and delineating attributes that have persisted despite different country contexts and political regimes.